The formative nature of graduation travel - Chang Liu; Ksenia Kirillova (Annals of Tourism Research Empirical Insights, 2021)
Graduation travel, or a trip taken after completion of undergraduate studies, is a niche phenomenon. Given the dearth of research on graduation travel, this study is first to investigate the stage-specific identity formation when a sense of self is initially established. Underpinned by the dual-cycle theory, the study considered two dimensions of identity consolidation - exploration in-depth and identification with commitment. Based on the survey with 393 Chinese university graduates, five benefits sought emerged: Social Fulfillment, Self-efficacy Improvement, Escape/Relaxation, Interest Pursuit, and Self-esteem Enhancement. Social Fulfillment and Self-Esteem had a positive effect on Exploration in-Depth, while Self-esteem Enhancement and Self-efficacy Improvement positively influenced Identification with Commitment. Tourism industry over-delivers on Escape/Relaxation and under-delivers on other benefits.
Keywords: 330; Benefits sought; Benefits found; Identity formation; Graduation trip; China